Magnetohydrodynamic mixer of an electrolyte solution - Gorobets, Svetlana; Gorobets, Oksana; Goyko, Iryna; Mazur, Sergey (My University, 2004)
Intensification of extraction of hexavalent chromium from solution was revealed in a magnetic field. It was shown that rate of both cementation and biosorption processes increases in a constant magnetic field due to magnetohydrodynamic stirring of the solution in the vicinity of steel matrix.
Keywords: magnetohydrodynamic stirring effect; магнітогідродинамічне перемішування; магнитогидродинамическое перемешивание; cementation; magnetic fields; цементація; магнітне поле; цементация; магнитное поле; кафедра технології оздоровчих продуктів